Educational services for the residents of Baghdad (Journal of the College of Basic Education, 2022)
The research aims to show educational services for the residents of Baghdad Governorate. To achieve this it is depend on standard score and by using descriptive method and quantitative analysis and using shapes to show the varability of the distribution. The research shows the effect of the population size on the variation in the distribution of educational services, where the highest rates of educational services was in the area of ​​(New Baghdad, Al-Maamoun, Al-Fahhama, and Al-Mansour) with rates (20.6%, 12.3%, 6.4%, 4.4%) and decreased in Al-Abaiji by (0.3%). The governorate recorded a decrease in the number of schools to record the ratios of guest schools (34.2%), which number (1315) and (2902) schools , and the student / teacher ratio (20.3) recorded the highest rate in Al-Kadhimiya with a rate of (39) and below in Al-Abaiji ( 9), and the rate for the student / department (38.0) recorded the highest in unit (63) and lowest in Mansour (34), and the average student’s rate (553) for the governorate raised in Al-Mamoun at a rate of (984) and below (223).